Exosome: A megastar of future cancer personalized and precision medicine - Rajib Dhar; Sukhamoy Gorai; Arikketh Devi; Saurabh Kumar Jha; Md. Atiar Rahman; Athanasios Alexiou; Marios Papadakis (Wiley, 2023)
Abstract Extracellular vesicles (EVs) are an innovative orientation of next‐generation cancer medicine. In EVs, the exosome is the most exciting domain associated with cancer research current decade.Exosomes have both cancer progression related and cancer healing capabilities depending on the source. It develops a new platform for cancer personalized and precision medicine visionary project to come to reality.